On the efficiency of spiral gyrotropic thermoelements in cooling mode - Zakharchuk, T.V.; Konstantynovych, I.A.; Konstantynovych, A.V.; Forbatiuk, A.V. (Journal of Thermoelectricity, 2019)
In this paper, the characteristics of BiSb, Ag2Tе and InSb materials in constant magnetic field were considered. Analytical and numerical methods were used to study the basic relations for the calculation of optimal parameters of spiral gyrotropic thermoelements in cooling mode. The dependences of maximum temperature difference for gyrotropic thermoelements of various shapes were obtained. It was shown that at constant magnetic fields the use of BiSb is more reasonable in the temperature range of 80-120 K, whereas in the range of 200 – 300 K it is worthwhile to use Ag2Tе. Bibl. 25, Tabl. 2, Fig. 14.